PENGARUH UMUR KAWIN PERTAMA TERHADAP TINGKAT FERTILITAS WANITA USIA SUBUR DI PROVINSI BANTEN BERDASARKAN ANALISIS LANJUT SDKI 2017 - Daini zulmi; Deden Gumilar Nugraha (Jurnal Medikes (Media Informasi Kesehatan), 2022)
The government is trying to reduce the fertility rate so that population spikes can be prevented; data in Indonesia shows that 72 per cent of women aged 15-49 years are already married. Marriage affects the likelihood of a woman being exposed to the risk of pregnancy; women who first married at a young age tend to start having children at a young age and have high fertility (SDKI 2017). This study aims to determine whether the age at first marriage affects the fertility rate of women of childbearing age in Banten Province. This method used a cross-sectional design. The analysis was conducted using the chi-square test and multivariate analysis using logistic regression analysis. The study's results showed that the number of children born alive second children was 5.7% in women of childbearing age. The results of the multivariate analysis prove that there is an effect between the age at first marriage and the fertility rate in women of childbearing age in Banten Province in 2017. Women who married for the first time at the age of 8-17 years have a 13 times higher risk of bearing children> 2 people than women. Who married for the first time aged> 18 years. Policy recommendations to increase CIE (Communication, Information and Education) activities regarding the MAM (Marriage Age Maturing) program can be intensified, especially through field cadres.